When Hotel Guests Complain About Tobacco, Electronic Cigarettes, and Cannabis: Lessons for Implementing Smoking Bans - Elizabeth AD Weigel; Georg E Matt (SAGE Publishing, 2022)
We analyzed reviews on tripadvisor.com from a random sample of N = 477 hotels in ten large cities in the US to examine how well existing policies protect guests from exposure to tobacco, electronic cigarette, and cannabis (TEC) smoke. We examined the association between complaints per 100 reviews with hotel smoking policies, star rating, cost, brand, and location. Of all TEC complaints, 80% were associated with thirdhand smoke residue lingering in hotels from previous guests. Compared to the hotel brands with the best records, the two worst-performing brands had 3.4- and 3.6-times higher complaint rates ( P < .001). Hotels with ≤2-star ratings had twice the complaints as higher-rated hotels ( P < .001). Compared to 100% smokefree hotels, those offering designated smoking rooms had a 35% higher rate of complaints ( P < .05). The success of some hotel brands demonstrates it is feasible to protect guests by fully committing to, implementing, and enforcing 100% smokefree building policies.